Survey of Librarians' Motivation in Writing Scientific Papers during the COVID-19 Pandemic: A Case Study - Pambayun, Kuncoro Galih (Department Library of Governance Institut of Home Affairs, 2022)
Background: The creation of scientific papers is the main job of librarians, who are often neglected due to busy technical work. During the COVID-19 pandemic, the Work From Home (WFH) policy provided librarians with more free time to write scientific papers. Objective: This study aimed to determine the motivation of librarians on the Whatsapp Group